The libertarian model of the economic system: genesis, evolution, prospects - Sashcheko, Roman S. (Journal of the Belarusian State University. Philosophy and Psychology, 2021)
The article is devoted to the genesis and evolution of the libertarian trend in the form of anarcho-syndicalism, as well as the libertarian model of the economic system. The author reveals the significance of the theoretical and methodological works of M. Stirner, P.-J. Proudhon, M. Bakunin and P. Kropotkin, whose ideas influenced the formation of anarcho-syndicalism, which is assigned a special role in the construction of libertarian socialism. The author reconstructs N. Chomsky’s views on the forms of social structure and the essence of state institutions. The main provisions of the libertarian economic system − ParEcon – are presented. The author substantiates the libertarian-socialist model of economic development of society as an alternative to the modern capitalist system.
Keywords: economy; libertarian socialism; capitalism; anarcho-syndicalism; anarcho-collectivism; anarcho-communism; mutualism; social and economic inequality; ParEcon; participatory economy; anarchism